2023
DOI: 10.1007/s10067-023-06577-w
|View full text |Cite
|
Sign up to set email alerts
|

Negative ANA-IIF in SLE patients: what is beyond?

Abstract: The antinuclear antibody (ANA) test has high sensitivity in diagnosing and classifying systemic lupus erythematosus (SLE). Objectives To describe the immunological pattern of SLE patients through investigating specific antinuclear autoantibodies by enzyme dot immunoassay and studying their frequency in both positive and negative ANA indirect immunofluorescence assay (IIF) cases. Methods In a cross-sectional study, blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Indirect immunofluorescence (IIF) antinuclear antibodies (ANAs) testing is a sensitive assay recommended in screening test for autoimmune systemic rheumatic disease (SARD) [1][2][3][4]. However, it was reported that ANA can be positive in healthy individuals up to 20%, and positivity in the majority of cases might be associated with anti-DFS70 antibodies [5][6][7] .…”
Section: Introductionmentioning
confidence: 99%
“…Indirect immunofluorescence (IIF) antinuclear antibodies (ANAs) testing is a sensitive assay recommended in screening test for autoimmune systemic rheumatic disease (SARD) [1][2][3][4]. However, it was reported that ANA can be positive in healthy individuals up to 20%, and positivity in the majority of cases might be associated with anti-DFS70 antibodies [5][6][7] .…”
Section: Introductionmentioning
confidence: 99%